Serum albumin combined with high-density lipoprotein cholesterol as a novel marker to predict coronary heart disease: are their associations multiplicative or rateable? - He, Li; Chen, Sisi; Zhu, Xuan; He, Fang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary heart disease (CHD) is a leading cause of death and disability worldwide. Albumin (ALB) and high-density lipoprotein cholesterol (HDL-c) possess potential clinical application values. However, the relationship between ALB*HDL-c (AHM) and CHD in the general population has not been studied yet. Therefore, this study aims to investigate the association between the AHM and CHD.MethodsWe conducted a retrospective study using data from 2,568 patients with a diagnosis of CHD from Wuhan Fourth Hospital. Patients with one or more major coronary artery or branch vessel stenosis ≥ 50% were included in the CHD group, while patients without CHD were enrolled in the control group. Logistic regression analysis was performed to determine the influence of AHM on CHD. The receiver operating characteristic (ROC) curve was constructed to analyze the predictive value of AHM for CHD.ResultsA total of 1,824 enrolled patients (71.0%) were diagnosed with CHD. The mean age was 64.56 ± 10.08 years. Notably, the CHD group had a substantially lower median AHM than that of the control group (36.94 vs. 52.63), with a statistically significant difference (P < 0.05). Specifically, logistic regression demonstrated that AHM was an independent risk factor for CHD (OR = 0.903, 95% CI: 0.888–0.918) in identifying CHD. In ROC analysis, the area under the ROC curve (AUC) for AHM [0.808 (95% CI: 0.791–0.825, P < 0.001)] was larger than that for ALB, HDL-c, and ALB–HDL-c ratio (AHR), and the differences were statistically significant (P < 0.05). Additionally, the Gensini (GS) score was negatively correlated with AHM (R = −0.150, P < 0.001). AHM was significantly associated with multivessel CHD (OR = 0.903, 95% CI: 0.888–0.918), and ROC analysis showed an AUC of 0.639 for AHM in predicting multivessel CHD.ConclusionAHM was significantly linked to an elevated risk of CHD. The lower the AHM level, the greater the CHD occurrence rate. AHM is associated not only with the occurrence of CHD but also with the severity of coronary artery stenosis. This underscores the crucial value of AHM in the discrimination and management of CHD.